Geology and Mineralization of the Kipawa Yttrium Zirconium Prospect, Quebec (256868fb-eca1-4603-a81a-284b103e7728) - James F. Allan (Canadian Institute of Mining, Metallurgy and Petroleum, 1992)
"The Kipawa yttrium-zirconium prospect is located about 150 km south of Noranda, Quebec. Yttrium-zirconium mineralization occurs in an elongate, regionally metamorphosed and deformed peralkaline complex in the Grenville terrain. The mineralized zone, as defined by =.0.10% Y2O3, is 1300 m long and 10 m to 30 m wide. Zirconium content typically ranges from 0.50 to 1.20% ZrO2, The mineralized zone strikes northwest and dips 20 degrees to 35 degrees to the southwest. It occurs at the structural base of the peralkaline complex in syenite gneiss and calc-silicate rocks and is conformable with both the footwall contact of the complex, and the layering and gneissosity in the enclosing rocks. Minerals of economic interest are eudialyte (sodium-zirconium silicate), mosandrite (sodium-titanium silicate), britholite (calcium-silica phosphate), and a few other uncommon zirconium and titanium silicate minerals.The highest and most continuous yttrium grades occur in the upper part of the syenite gneiss unit in areas containing eudialyte, mosandrite and minor britholite. Yttrium also occurs in britholite in calc-silicate rocks and in mosandrite in syenitic rocks in the lower part of the syenite gneiss unit. Both the yttrium-bearing minerals and yttrium grades are erratic in the lower part of the unit. Zirconium is generally more uniformly distributed than yttrium. A peralkaline granite gneiss phase of the complex intrudes the syenite gneiss and possibly truncates it, and the mineralization, near the southern boundary of the mineralized zone.The mineralized zone is coincident with a radiometric anomaly and discontinuous yttrium and zirconium soil anomalies.More drilling and metallurgical studies will be required to determine the economic viability of the yttrium and zirconium mineralization at Kipawa."